Musical Empathy, Emotional Co-Constitution, and the “Musical Other” - Peters, Deniz (Empirical Musicology Review, 2015)
Musical experience can confront us with emotions that are not currently ours. We might remain unaffected by them, or be affected: retreat from them in avoidance, or embrace them and experience them as ours. This suggests that they are another’s. Whose are they? Do we arrive at them through empathy, turning our interest to the music as we do to others in an interpersonal encounter? In addressing these questions, I differentiate between musical and social empathy, rejecting the idea that the emotions arise as a direct consequence of empathizing with composers or performers. I argue that musical perception is doubly active: bodily knowledge can extend auditory perception cross-modally, which, in turn, can orient a bodily hermeneutic. Musical passages thus acquire adverbial expressivity, an expressivity which, as I discuss, is co-constituted, and engenders a “musical other.” This leads me to a reinterpretation of the musical persona and to consider a dialectic between social and musical empathy that I think plays a central role in the individuation of shared emotion in musical experience. Musical empathy, then, occurs via a combination of self-involvement and self-effacement—leading us first into, and then perhaps beyond, ourselves.